The Effect of Cabbage Waste Concentration and Fermentation Time on The Decaffeination of Arabica Coffee - Hariyadi, Tri; Keryanti, Keryanti; Asih, Ria Puspa; Ahmad, Zidni Zakiyyah (Bandung State Polytechnic (Politeknik Negeri Bandung), 2024)
The purpose of this study was to determine the effect of the concentration of cabbage waste and fermentation time on the caffeine content reduction of Arabica coffee from Pangalengan. Decaffeination is carried out using a wet fermentation method using protease enzyme activity produced by lactic acid bacteria from cabbage waste. Protease enzymes can break down the slime layer on coffee beans so that caffeine is decomposed through the esterification process to become chlorogenic acid. Fermentation was carried out anaerobically in a fermenter with a capacity of ± 2L with a fermentation time of 72 hours and sampling every 6 hours. The concentration of cabbage waste ranged from 10-80% (w/w). Arabica coffee beans were tested for caffeine content (%) using a UV-Vis spectrophotometer. According to the study's findings, the caffeine level decreases as the concentration of cabbage waste increases. Meanwhile, the caffeine level decreases as fermentation time increases. The addition of 80% concentration of cabbage waste with 48 hours of fermentation time produced the optimum results for the Arabica coffee decaffeination process. This method achieved a decaffeination efficiency of more of 96% and met the quality standards outlined in SNI 01-3542-2004.